2021
DOI: 10.1016/j.ebiom.2021.103209
|View full text |Cite
|
Sign up to set email alerts
|

Renal interstitial fibroblasts coproduce erythropoietin and renin under anaemic conditions

Abstract: Background Erythrocyte mass contributes to maintaining systemic oxygen delivery and blood viscosity, with the latter being one of the determinants of blood pressure. However, the physiological response to blood pressure changes under anaemic conditions remain unknown. Methods and Findings We show that anaemia decreases blood pressure in human patients and mouse models. Analyses of pathways related to blood pressure regulation demonstrate that anaemia enhances the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…In contrast, severe hypoxia and ROX stimulate Epo production through renal erythropoietin producing (REP) cells [ 34 , 39 , 40 , 41 , 42 , 43 , 44 ] and increase the plasma Epo concentration. Our immunohistochemistry showed that both ROX and severe hypoxia increase Epo production by interstitial cells but not by tubular cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, severe hypoxia and ROX stimulate Epo production through renal erythropoietin producing (REP) cells [ 34 , 39 , 40 , 41 , 42 , 43 , 44 ] and increase the plasma Epo concentration. Our immunohistochemistry showed that both ROX and severe hypoxia increase Epo production by interstitial cells but not by tubular cells.…”
Section: Discussionmentioning
confidence: 99%
“…Because blood pressure and fluid volume are principally controlled by the renin-angiotensin-aldosterone system (RAAS), [32][33][34] we investigated the expression of RAAS-related genes. Of renal RAAS-related genes, the expression of Ren1 and Ace2 (encoding renin and angiotensin-converting enzyme 2, respectively) genes was altered by space travel, whereas that of Agtr1 and Ace (encoding angiotensin receptor 1 and angiotensin-converting enzyme 1, respectively) genes was not b a s i c r e s e a r c h 3a).…”
Section: Effects Of Space Travel On Renal Expression Of Genes Related To Blood Pressure Controlmentioning
confidence: 99%
“…This protocol describes how to efficiently isolate living interstitial fibroblasts from mouse kidneys and expand them in ex vivo cultivation. Because a subset of interstitial fibroblasts in the renal cortex, which are referred to as renal erythropoietin (Epo)-producing (REP) cells, play key roles in Epo production, renin production and kidney fibrosis ( Obara et al., 2008 ; Souma et al., 2013 , 2016 ; Suzuki and Yamamoto, 2016 ; Miyauchi et al., 2021 ), this protocol features the manipulation of REP cells. This protocol was established using a genetically modified mouse line in which REP cells were efficiently labeled with the tdTomato red fluorescent protein via the transgene expression of Cre recombinase under the control of mouse Epo gene regulatory regions ( Yamazaki et al., 2013 ; Suzuki et al., 2016 ).…”
Section: Before You Beginmentioning
confidence: 99%
“…Following this protocol, we collected approximately 3000 primary REP cells on average from the kidneys of an adult REP cell-labeled mouse ( Yamazaki et al., 2013 ). Sufficient amounts (1×10 5 cells) of cells for reverse transcription-quantitative PCR (RT-qPCR) analyses were collected by repeating steps 1–19 of this protocol ( Souma et al., 2013 ; Miyauchi et al., 2021 ). Alternatively, to conduct RT-qPCR analyses with a small number of REP cells, a CellAmp Whole Transcriptome Amplification Kit (Takara, Cat# 3734) was successfully used.…”
Section: Expected Outcomesmentioning
confidence: 99%
See 1 more Smart Citation